CARIBIC aircraft measurements of Eyjafjallajökull volcanic clouds in April/May 2010 - Rauthe-Schöch, A.; Weigelt, A.; Hermann, M.; Martinsson, B.G.; Baker, A.K.; Heue, K.-P.; Brenninkmeijer, C.A.M.; Zahn, A.; Scharffe, D.; Eckhardt, S.; Stohl, A.; van Velthoven, P.F.J. (München : European Geopyhsical Union, 2012)
The Civil Aircraft for the Regular Investigation of the Atmosphere Based on an Instrument Container (CARIBIC) project investigates physical and chemical processes in the Earth's atmosphere using a Lufthansa Airbus long-distance passenger aircraft. After the beginning of the explosive eruption of the Eyjafjallajökull volcano on Iceland on 14 April 2010, the first CARIBIC volcano-specific measurement flight was carried out over the Baltic Sea and Southern Sweden on 20 April. Two more flights followed: one over Ireland and the Irish Sea on 16 May and the other over the Norwegian Sea on 19 May 2010. During these three special mission flights the CARIBIC container proved its merits as a comprehensive flying laboratory. The elemental composition of particles collected over the Baltic Sea during the first flight (20 April) indicated the presence of volcanic ash. Over Northern Ireland and the Irish Sea (16 May), the DOAS system detected SO2 and BrO co-located with volcanic ash particles that increased the aerosol optical depth. Over the Norwegian Sea (19 May), the optical particle counter detected a strong increase of particles larger than 400 nm diameter in a region where ash clouds were predicted by aerosol dispersion models. Aerosol particle samples collected over the Irish Sea and the Norwegian Sea showed large relative enhancements of the elements silicon, iron, titanium and calcium. Non-methane hydrocarbon concentrations in whole air samples collected on 16 and 19 May 2010 showed a pattern of removal of several hydrocarbons that is typical for chlorine chemistry in the volcanic clouds. Comparisons of measured ash concentrations and simulations with the FLEXPART dispersion model demonstrate the difficulty of detailed volcanic ash dispersion modelling due to the large variability of the volcanic cloud sources, extent and patchiness as well as the thin ash layers formed in the volcanic clouds. publishedVersion